A content analysis of the Orbeez® Gel Blaster injury challenge on TikTok - Hannah P. Schneider; Jamie M. Reedy; Rebecca J. McAdams; David I. Swedler; Jennifer A. Manganello; Kristin J. Roberts; Leah K. Middelberg; Lara B. McKenzie (Injury Epidemiology)
Abstract Background TikTok is one of the fastest-growing social media platforms. With 50 million active daily users in the United States, videos on TikTok have the opportunity to reach an exceptionally large audience. It is of concern that some of these videos may be harmful, especially if they encourage dangerous or risky behavior that can increase injury risk. This is common for social media challenges, where people are encouraged to participate in and record a task and then post it on social media. The “Orbeez Challenge” was a challenge that went viral in 2022 and encouraged viewers to shoot water beads with Gel Blaster guns at others. The purpose of this study was to describe content for the “Orbeez Challenge” on TikTok, informed by pathways of the Elaboration Likelihood Model (ELM). Methods This study conducted a content analysis of TikTok videos related to the Orbeez challenge identified between October 5–11, 2022. A codebook was created by using abductive code generation, driven by an inductive iterative review of a sample of videos not included in the final study sample, and deductive code development to collect elements of the ELM. Results There were 125 videos in the final sample. Collectively, these videos had over 255 million views. Most (70.0%) of the creators were laypersons. Text (n = 97; 77.6%) and music (n = 83; 66.4%) were frequently present in the videos. Individuals were primarily shooting (47.2%) or loading (25.6%) the Gel Blaster. Nearly half (46.3%) of the content creators had between 10,000 and 500,000 followers. Most videos (n = 109; 87.2%) did not depict any injury prevention precautions, but of the 15 videos (12.0%) that did show injury prevention precautions, 14 (93.3%) were for eye protection. Conclusions This study characterized the content of the TikTok videos associated with the viral “Orbeez Challenge” and showed that TikTok videos could be characterized with guidance from a health communication theory. Despite their increased injury risk, the videos had high engagement and were most frequently posted by laypersons. This research presents an opportunity for countering injury challenges on social media and can guide injury professionals in designing and improving virtual health education campaigns.